Koyunlarda phlorhizinle oluşturulan ketazisin riboflovin ve niacin seviyelerine etkisi - Abdullah Başoğlu; Kürşat Turgut; Mursayettin Eksen; Bünyamin Traş; Mehmet Maden; Mahmut Ok; A. Levent Baş; Ercan Keskin (Eurasian Journal of Veterinary Sciences)
Six non-lactating, non-pregnant adult ewes divided into two groups of 3 animal each as a control and experimental groups were u sed to evaluate the effect of phlorhizin-induced ketosis on plasma and rumen fluid riboflavin and niacin concentrations. The me an pH values and the counts of protozoa and bacteria of the rumen fluid in experimental group did not change significantly (p>0.05). Alteration of plasma riboflavin concentration in experimental group w as not significant (p>O. 05). Whereas both plasma and rumen fluid niacin concentrations decreased from 5. 03 mc gl ml and 9. 53 mcg/ml to 2.39 mcg/ml and 2.41 mcglml respectively and decraements in both plasma and rumen fluid niacin concentrations were significant (p<0.05).